The Influence Of Playing Therapy And Music Therapy (Listening Al-Qur’an : Juz Amma) To Anxiety Respond At Toddler - Ghofar, Abdul; Ningsih, Lutfiyah (Unipdu Jombang, 2012)
ABSTRACT Child feels uncomfortable feeling, such as affraid, worry, painful, when treated at the hospital. It makes crisis, caused by many things, that are child development age, experiences of past disease, farewel or hospital treatment, support system and how dangerous the disease, also treatment threatening. Most effective media to express the feeling and can work along with officer of health during treatment is activity of gameor listening to the music. Â The result of the research shows that there are influences of both playing and listening music therapies. Before both therapies are given, anxiety respond shows all 15 get maladaptive (100%). After playing therapies was given for 3 days 10 children show adaptive (66,7%), as well for listening to music therapy get, 4 children that show adaptive signing. Based from t-test result with significant level ï??=0,012. Its means, there was influences of giving playing therapy and music therapy (listening to Al-Qurâ??an : Juz Amma) to decrease of anxiety respond at toddler children age. Â Playing therapy has better influences than music therapy, because when the therapy is being done, the children have more interact with the nurse. Parent support as well as nurses are needed as motivator for them in giving these therapies. Givin sicialization at the child and parent before entering the hospital, by orientation at treatment room, camber friend, giving both playing and listening to music therapies are very important to decrease anxiety response of child age of toddler. Â Keyword: Anxiety response of toddler, music therapy, playingtherapy.